POVERTY REDUCTION STRATEGIES IN ISLAM (Al-Mostansiriyah journal for Arab and international studies, 2018)
The study illustrates the twofold nature of poverty dynamics of eradication in the Islamic system, which unites (a) boosting income via a vital anti-hoarding and pro-investment Zakat system with (b) efficiently redistributing the revenues for the sake of the needy. The research specifies the distinct elements that balance those two aspects of the Islamic system to fight poverty, implies that development is all-embracing, sustainable, equitable, and free of deficiencies noted in other similar systems. These deficiencies consist of looking at poverty as an minor failure at any moment in time to get essential material requirements, and a failure to value these requirements are not the similar for all. The aims remain; introducing a theoretical outline, the poverty concept in Islam, conceptualize poverty from the perspective of Islam, focus on the flaws of the poverty concept in the existing literature, provide an overview of the development concept in Islam, and concentrate on how Islam views poverty? What measures are provided in Islam to combat poverty? What is the common denominator in Islam?. This study used a survey technique through studies conducted in the poverty reduction strategies in Islam in general and studies that are related to that in particular. The case studies mostly relied on reviewing and synthesizing on the verses from the Koran and the “hadith” based poverty, and conducting a number of interviews with specialists. Also a number of Islamic literatures were addressed, insofar as their direct or indirect impact on poverty. The study continues in highlighting the additional security nets established by Islam to liberate the poor people and their communities from the social, material, political and spiritual ills of poverty.